2019
DOI: 10.1097/bpo.0000000000001346
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Pin Tract Infections and Septic Arthritis in Percutaneous Distal Femur Pinning

Abstract: Background: Retrograde percutaneous pinning often involves intra-articular pin placement. Classic teaching has cautioned about the risk of septic arthritis with intra-articular pins, although an incidence has not been reported for this complication. The purpose of this study was to determine the incidence of pin tract infections and septic arthritis following retrograde percutaneous pinning of the distal femur. Methods: A retrospective review identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In addition, surgical disruption of the joint capsule facilitates communication between the inside and outside of the knee joint. Intra-articular pins can increase the risk of septic arthritis owing to communication with the joint 15. Mamoya et al reported a case of synovial fistula after femoral tension band plating for genu valgum correction 16.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, surgical disruption of the joint capsule facilitates communication between the inside and outside of the knee joint. Intra-articular pins can increase the risk of septic arthritis owing to communication with the joint 15. Mamoya et al reported a case of synovial fistula after femoral tension band plating for genu valgum correction 16.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of exposure to occupational factors for PTI is also not negligible, especially for agricultural practitioners in developing areas. The workload of heavy physical strength, the working environment of complex species of microorganisms, and work-related high-pressure psychological state may be associated with a high incidence of infectious diseases [ 12 , 29 , 33 , 34 ]. In this study, the rate of PTI was 35.4% in patients working in agriculture approximately.…”
Section: Discussionmentioning
confidence: 99%
“…And a retrospective study of 163 patients who underwent retrograde percutaneous pinning of the distal femur for osteotomy or physeal fracture was conducted by Murgai e al. [ 12 ] and reported the incidence of PTI was 6.7%. The previous studies commonly focused on the treatments of PTI and percentages of patients with complications, concentrated on the risk factors less.…”
Section: Introductionmentioning
confidence: 99%
“…When Steinmann pin fixation was selected, retrograde insertion was preferred with the majority electing to not bury the pins under the skin. Despite historical concerns of septic arthritis stemming from intra-articular pins, this appears extremely uncommon; however, localized pin site infection is not infrequent [19].…”
Section: Discussionmentioning
confidence: 99%